Why do voters forgive corrupt mayors? Implicit exchange, credibility of information and clean alternatives. Issue 4 (3rd July 2016) - Muñoz, Jordi; Anduiza, Eva; Gallego, Aina
ABSTRACT: Corruption cases have limited electoral consequences in many countries. Why do voters often fail to punish corrupt politicians at the polls? Previous research has focused on the role of lack of information, weak institutions and partisanship in explaining this phenomenon. In this paper, we propose three micro-mechanisms that can help understand why voters support corrupt mayors even in contexts with high information and strong institutions: implicit exchange (good performance can make up for corruption), credibility of information (accusations from opposition parties are not credible) and the lack of credible alternatives (the belief that all politicians are corrupt). We test these mechanisms using three survey experiments conducted in Catalonia. Our results suggest that implicit exchange and credibility of information help explain voters' support for corrupt politicians.